Cryo‐Electron Microscopy: Cryo‐EM‐On‐a‐Chip: Custom‐Designed Substrates for the 3D Analysis of Macromolecules (Small 21/2019). Issue 21 (24th May 2019) - Alden, Nick A.; Varano, A. Cameron; Dearnaley, William J.; Solares, Maria J.; Luqiu, William Y.; Liang, Yanping; Sheng, Zhi; McDonald, Sarah M.; Damiano, John; McConnell, Jennifer; Dukes, Madeline J.; Kelly, Deborah F.
Abstract : In article number1900918, Deborah F. Kelly and co‐workers develop a new cryo‐electron microscopy (EM)‐on‐a‐chip approach. This strategy enables researchers to directly visualize the "fault in our stars" regarding cancer proteins. The structural assemblies of p53 from brain cancer cells are determined for the first time using the microchip‐based technique. Artistic rendition by Daryl N. Branford.